Study on the Efficacy of Plant Growth Promoting Microbes on Seed Germination and Disease Control of Melia dubia in Nursery - Sreedhar, S. S.; Mohan, V. (Indian Forester, 2016)
An experiment was conducted to test the efficacy of different bio-fertilizers such as Arbuscular Mycorrhizal (AM) fungi and Plant Growth Promoting Rhizobacteria (PGPR)) individually and in combinations on seed germination and survival of seedlings of Melia dubia, an economically important fast growing native tree species against the plant pathogenic fungus, Fusarium oxysporum causing root rot disease in tree nurseries. It was observed that application of bio-fertilizers individually and in different combinations showed increased seed germination, better survival and growth of seedlings of M. dubia even in the presence of the root rot pathogen, F. oxysporum. Maximum percentage of seed germination was recorded in combined application of all four bio-fertilizers along with Fusarium in M. dubia. This was followed by dual application of AMF + Azoto + Fusarium.